Novel DNA fluorescence probes based on 2-thioxo-tetrahydro-4H-imidazol-4-ones: synthetic and biological studies - Majouga, Alexander G.; Udina, Anna V.; Beloglazkina, Elena K.; Skvortsov, Dmitrii A.; Zvereva, Maria I.; Dontsova, Olga A.; Zyk, Nikolay V.; Zefirov, Nikolay S. (Tetrahedron letters, 2012)
An efficient method for the liquid-phase synthesis of 3,5-disubstituted thiohydantoins has been developed. This new class of substituted thiohydantoins was tested as DNA fluorescence probes. Anthracene-substituted thiohydantoin undergoes a change in fluorescence in the presence of DNA. (C) 2011 Elsevier Ltd. All rights reserved.